A method for preparing nanocellulose / aramid fiber lithium battery separator material by heterogeneous process

The preparation of nanocellulose/aramid fiber lithium battery separator materials through heterogeneous processes solves the problems of existing separator materials being prone to deformation and poor breathability at high temperatures, achieving high mechanical strength and excellent electrolyte absorption rate, and improving the circulation and safety performance of lithium batteries.

CN114865218BActive Publication Date: 2025-03-18TAISHAN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210513425.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-12
Publication Date
2025-03-18
Estimated Expiration
2042-05-12

AI Technical Summary

Technical Problem

The existing lithium battery separator materials are prone to deformity at high temperatures and severe heat shrinkage, resulting in thermal runaway and explosion, and have poor breathability and wetting properties, which cannot meet the requirements of fast charging and discharging of lithium batteries.

Method used

The nanocellulose/aramid fiber lithium battery separator material is prepared by a heterogeneous process, and the inner and outer self-bonding micro-crosslinking structure is formed through spray mixing and bonding, which improves the mechanical strength of the separator and the electrolyte absorption rate.

Benefits of technology

It achieves high mechanical strength of the diaphragm, excellent electrolyte absorption rate and good thermal stability, and improves the circulation and safety performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 220512135611
    Figure 220512135611
  • Figure 220512135622
    Figure 220512135622
Patent Text Reader

Abstract

The present invention discloses a method for preparing a nanocellulose / aramid fiber lithium battery diaphragm material by a heterogeneous process. Nanocellulose with good lyophilicity and aramid fiber with excellent high temperature resistance are used to modify and prepare nanocellulose suspension and aramid fiber suspension respectively. Drawing on the papermaking molding principle and steel concrete structure function design, the suspensions are mixed and then added with polyimide solution for blending. The film is formed by suction filtration and solvent replacement and drying to obtain a blended film. Then, polyimide is used as a reinforcing agent to spray the surface of the membrane, and spray-mixing is combined to form an internal and external self-bonded micro-cross-linked structure. After drying, it is sprayed and dried for multiple times to prepare a nanocellulose / aramid fiber lithium battery diaphragm material. The lithium battery diaphragm prepared by the present invention has high strength, good thermal stability, excellent electrolyte wettability, and good electrochemical performance. It can fully meet the cycle performance and safety performance requirements of lithium batteries and has great application value and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium battery diaphragm material, in particular to a method for preparing a nano cellulose / aramid fiber lithium battery diaphragm material by a heterogeneous process, which is particularly suitable for use as a power lithium battery diaphragm. Background Art

[0002] With the promotion of green new energy in modern society, lithium-ion batteries are gradually being widely used in new energy vehicles represented by hybrid vehicles and pure electric vehicles, conforming to the development trend of the times. Therefore, the booming emerging markets have put forward higher requirements on the performance of lithium batteries, especially thermal safety performance. The diaphragm is one of the core components of lithium-ion batteries. It can control the transmission of ions and prevent internal short circuits of the battery. The performance of the diaphragm directly affects the cycle life and safety performance of the lithium battery. The cost of the diaphragm accounts for about 25% of the total cost of the lithium battery. Therefore, it is very important to develop a low-cost, high-safety diaphragm.

[0003] The thermal safety of the diaphragm (closed pore and rupture temperature) depends on the melting point of the diaphragm substrate. The melting points of most polyolefin membrane materials used in the market, such as PE, are 128-135°C and PP is 150-160°C. They are easily deformed at high temperatures and have severe thermal shrinkage, which leads to thermal runaway and explosion when the positive and negative electrodes are in direct contact, and cannot meet the safety requirements of high-power power batteries. The air permeability and wettability (liquid absorption, liquid retention and porosity) of polyolefin diaphragm materials are poor, which cannot meet the requirements of rapid charging and discharging of lithium batteries, affecting the cycle life of the battery.

[0004] Cellulose is the most widely sourced green renewable polymer material in nature. Compared with synthetic polymers, it is renewable, degradable, green and environmentally friendly, easy to modify, and has good biocompatibility. Its downstream product, nanocellulose, not only inherits these advantages, but also has high strength, high hydrophilicity, good electrolyte wettability, and can ensure high liquid absorption rate. However, it has high crystallinity and needs to be activated to improve surface accessibility. Aramid fiber is a new type of high-tech synthetic aromatic polyamide fiber. It has excellent properties such as ultra-high strength, long-lasting thermal stability, acid and alkali resistance, does not decompose or melt at 560°C, has good insulation and corrosion resistance, and can ensure high safety performance. Blending nanocellulose and aramid fiber can replace polyolefin diaphragm materials and ensure the thermal safety of lithium batteries. Summary of the invention

[0005] The present invention provides a method for preparing a nano-cellulose / aramid fiber lithium battery diaphragm material by a heterogeneous process. The method adopts a heterogeneous preparation process, draws on the papermaking forming principle and the steel concrete structure function design, and uses a spray-mixing combination method to form an internal and external self-bonded micro-cross-linked structure. First, nano-cellulose and aramid fiber suspensions are prepared separately, and after all are mixed, a polyimide solution is added to blend them. The blended solution is filtered through sheet making to form a film, and then the polyimide solution is further used to spray the surface of the blended film. After solvent replacement, drying, spraying and drying, a nano-cellulose / aramid fiber lithium battery diaphragm material with good performance is obtained.

[0006] To achieve the above purpose, the nanocellulose / aramid fiber lithium battery separator material prepared by the heterogeneous process of the present invention has a thickness of 100-350 μm, a mechanical strength of 5-55 MPa, an electrolyte absorption rate of 100-400%, a liquid retention rate of 50-250%, a porosity of 20-80%, a separator thermal shrinkage rate of 0.2-2% at 200°C, a thermal shrinkage force of 0.01-0.6N, an ionic conductivity of 0.5-1.5 mS / cm, and a discharge capacity of 150-170 mAh.g at 0.2C. -1 .

[0007] The technical solution adopted by the present invention is: a nano cellulose / aramid fiber lithium battery separator material of a heterogeneous process, using nano cellulose and aramid fiber, respectively modifying and preparing nano cellulose and aramid fiber suspensions, all of which are mixed and then added with a polyimide solution for blending, the blended solution is filtered through sheet making to form a membrane, and then the surface of the blended membrane is further sprayed with a polyimide solution, and after solvent replacement, drying, spraying and drying processes, a nano cellulose / aramid fiber lithium battery separator material with excellent performance is obtained.

[0008] The nanocellulose is nanocellulose extracted from one or more mixed pulps of cotton pulp, wood pulp, bamboo pulp or grass pulp.

[0009] The aramid fiber is one or more mixed fibers selected from pulp, short cuts, staple fibers and dry powder of para- or meta-aromatic aramid fibers.

[0010] The polyimide is one of water-soluble polyimide, homophenyl polyimide, polyamide-imide or polyetherimide.

[0011] The above-mentioned method for preparing the nanocellulose / aramid fiber lithium battery separator material by the heterogeneous process comprises the following steps:

[0012] (1) Preparation of nanocellulose suspension: First prepare a mixed solution of nanocellulose / cationic polyacrylamide / diatomaceous earth, then add solid acid and stir evenly to obtain a suspension. The mass percentage of each component of the suspension is 0.1-0.9% nanocellulose, 0.001%-0.009% cationic polyacrylamide, 0-0.1% diatomaceous earth, 0-10% solid acid, and water is added. The stirring time is 0.5-2h, the stirring temperature is 80-115°C, and the rotation speed is 700-1200rpm;

[0013] (2) Preparation of aramid fiber suspension: prepare an alkaline suspension of aramid fiber / polyethylene oxide, the mass percentage of each component of the suspension is aramid fiber 0.3-0.7%, polyethylene oxide 0-0.02%, strong alkali 0.4%-0.6%, and water to make up. The stirring time is 0.5-2h, the stirring temperature is 20-40°C, and the rotation speed is 200-300rpm;

[0014] (3) Preparation of a blended membrane: after mixing all the suspensions obtained in steps (1) and (2), a polyimide solution is added for blending, wherein the concentration of the polyimide solution is 0 to 20%, the mass ratio of polyimide to nanocellulose / aramid fiber is 0 to 5.5:1, and the blending time is 30 to 60 min; then the blended solution is sheeted and filtered to form a membrane, and a nanocellulose / aramid fiber blended membrane is obtained through solvent replacement and drying processes, wherein the solvent replacement time is 0.25 to 4 h, the drying time is 0.75 to 1.5 h, and the drying temperature is 60 to 90 ° C.;

[0015] (4) Surface spraying treatment of the blended membrane: spray the polyimide solution in step (3) on the surface of the blended membrane obtained in step (3), and then spray it several times after drying to finally obtain a nanocellulose / aramid fiber lithium battery separator. The number of spraying times is 1 to 4 times, the drying time is 20 to 60 minutes, and the drying temperature is 80 to 110°C.

[0016] In the step (1), a solid acid is used for carboxylation, and the solid acid used is a dicarboxylic acid, such as glutaric acid, adipic acid or azelaic acid.

[0017] In the step (1), the cationic polyacrylamide is a dry powder having an ionicity between 40 and 60.

[0018] The diatomaceous earth in step (1) is a kind of siliceous rock formed by the sedimentation of diatom remains, and has a particle size of 5 to 20 microns.

[0019] The strong base in step (2) is one of sodium hydroxide, potassium hydroxide or potassium tert-butoxide.

[0020] The polyethylene oxide in step (2) is a water-soluble polymer with a relative molecular weight of 1 to 4 million.

[0021] The solvent in step (3) is one of methanol, ethanol or isopropanol.

[0022] The beneficial effects of the present invention are as follows: the blended membrane is prepared by blending nanocellulose and aramid fiber, and the structural function design is imitated by steel concrete, with high mechanical strength and excellent wettability; the heterogeneous process draws on the principle of papermaking, and the film is formed by sheeting and filtration, and the preparation process is simple and green and environmentally friendly; polyimide is used as a reinforcing agent, and a spray-mixing combination method is adopted to form an internal and external self-bonded micro-cross-linked structure, which has good compatibility and high bonding strength; the prepared nanocellulose / aramid fiber lithium battery diaphragm material has good thermal stability, excellent wettability, high porosity, and excellent electrochemical performance, which is conducive to improving the cycle performance and safety performance of the battery. This method can replace traditional polyolefin diaphragm materials, and can be applied to the lithium battery market to achieve high-value utilization of biomass materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a graph of thermal shrinkage force and thermal shrinkage rate of Examples 1-3 of the present invention; Figure 2 It is a comparison chart of the electrochemical cycle stability of Example 2 of the present invention and a commercial polyethylene diaphragm. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and beneficial technical effects of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments.

[0025] Example 1 Preparation of nanocellulose / aramid fiber lithium battery separator material by heterogeneous process

[0026] Step 1: Prepare nanocellulose suspension. First prepare a mixed solution of nanocellulose / cationic polyacrylamide / diatomaceous earth, then add glutaric acid and stir evenly to obtain a suspension. The mass percentage of each component of the suspension is 0.3% nanocellulose, 0.001% cationic polyacrylamide, 0.025% diatomaceous earth, 2.5% glutaric acid, and water is added. The stirring time is 30 minutes, the stirring temperature is 80°C, and the rotation speed is 800rpm to obtain a nanocellulose suspension, which is cooled to room temperature for use;

[0027] Step 2: Prepare aramid fiber suspension. Prepare an alkaline suspension solution of aramid fiber / polyethylene oxide. The mass percentage of each component of the suspension is 0.1% of meta-aramid chopped fiber, 0.4% of para-aramid pulp fiber, 0.01% of polyethylene oxide and 0.55% of potassium tert-butoxide, and water is added. The stirring time is 30 minutes, the stirring temperature is 20°C, and the rotation speed is 200 rpm to obtain an aramid fiber suspension;

[0028] Step 3: Prepare the blended membrane. Mix all the obtained nanocellulose and aramid fiber suspensions, add 10% polyimide solution for blending, the mass ratio of polyimide to nanocellulose / aramid fiber is 1:1, and the blending time is 30 minutes; filter the blended solution into a membrane, then soak it in methanol solution for 15 minutes, and hot-press and dry it at 70°C for 0.75 hours to obtain a nanocellulose / aramid fiber blended membrane;

[0029] Step 4: Spraying treatment: Spray the polyimide solution on the surface of the blended film, with a drying temperature of 80° C. and a drying time of 20 min. After drying, a nanocellulose / aramid fiber lithium battery separator material is finally obtained.

[0030] Example 2 Preparation of nanocellulose / aramid fiber lithium battery separator material by heterogeneous process

[0031] Step 1: Prepare nanocellulose suspension. First prepare a mixed solution of nanocellulose / cationic polyacrylamide / diatomaceous earth, then add adipic acid and stir evenly to obtain a suspension. The mass percentage of each component of the suspension is 0.5% nanocellulose, 0.003% cationic polyacrylamide, 0.05% diatomaceous earth, 5% adipic acid, and water to make up. The stirring time is 60 minutes, the stirring temperature is 95°C, and the rotation speed is 1000rpm to obtain a nanocellulose suspension, which is cooled to room temperature for use;

[0032] Step 2: Prepare aramid fiber suspension. Prepare an alkaline suspension solution of aramid fiber / polyethylene oxide. The mass percentage of each component of the suspension is 0.15% of meta-aramid chopped fiber, 0.35% of para-aramid pulp fiber, 0.015% of polyethylene oxide and 0.55% of sodium hydroxide, and water is added. The stirring time is 60 minutes, the stirring temperature is 30°C, and the rotation speed is 250rpm to obtain an aramid fiber suspension;

[0033] Step 3: Prepare the blended membrane. Mix all the obtained nanocellulose and aramid fiber suspensions, add 15% polyimide solution for blending, the mass ratio of polyimide to nanocellulose / aramid fiber is 2:1, and the blending time is 45 minutes; filter the blended solution into a membrane, then soak it in an ethanol solution for 30 minutes, and heat-press and dry it at 80°C for 0.75 hours to obtain a nanocellulose / aramid fiber blended membrane;

[0034] Step 4: Spraying: Spray the polyimide solution on the surface of the blended film, with a drying temperature of 105°C and a drying time of 40 minutes. Repeat the operation twice, and finally obtain the nanocellulose / aramid fiber lithium battery separator material after drying.

[0035] Example 3 Preparation of nanocellulose / aramid fiber lithium battery separator material by heterogeneous process

[0036] Step 1: Prepare nanocellulose suspension. First prepare a mixed solution of nanocellulose / cationic polyacrylamide / diatomaceous earth, then add azelaic acid and stir evenly to obtain a suspension. The mass percentages of the components of the suspension are 0.7% nanocellulose, 0.005% cationic polyacrylamide, 0.075% diatomaceous earth, 7.5% azelaic acid, and water. The stirring time is 90 minutes, the stirring temperature is 110°C, and the rotation speed is 1200rpm to obtain a nanocellulose suspension, which is cooled to room temperature for use;

[0037] Step 2: Prepare aramid fiber suspension. Prepare an alkaline suspension solution of aramid fiber / polyethylene oxide. The mass percentage of each component of the suspension is 0.25% of meta-aramid chopped fiber, 0.25% of para-aramid pulp fiber, 0.02% of polyethylene oxide and 0.55% of potassium hydroxide, and water is added. The stirring time is 90 minutes, the stirring temperature is 40°C, and the rotation speed is 300 rpm to obtain an aramid fiber suspension;

[0038] Step 3: Prepare the blended membrane. Mix all the obtained nanocellulose and aramid fiber suspensions, add 20% polyimide solution for blending, the mass ratio of polyimide to nanocellulose / aramid fiber is 3:1, and the blending time is 60 minutes; filter the blended solution into a membrane, then soak it in isopropanol solution for 1 hour, and hot-press and dry it at 90°C for 1.25 hours to obtain a nanocellulose / aramid fiber blended membrane;

[0039] Step 4: Spraying: Spray the polyimide solution on the surface of the blended film, with a drying temperature of 105°C and a drying time of 40 minutes. Repeat the operation 3 times, and finally obtain the nanocellulose / aramid fiber lithium battery separator material after drying.

[0040] The lithium battery separator materials produced in Examples 1-3 were tested: the thickness was 200-350 μm, the mechanical strength was above 20 MPa, the electrolyte absorption rate was above 150%, the liquid retention rate was above 80%, the porosity was 40-60%, the thermal shrinkage rate of the separator at 200°C was less than 1%, the thermal shrinkage force was less than 0.15 N, the ionic conductivity was above 1 mS / cm, and the discharge capacity at 0.2C was 160 mAh.g -1 It can be seen that the diaphragm material produced by the present invention has good thermal stability, high liquid absorption rate, good mechanical properties, excellent electrochemical properties and relatively ideal safety performance.

[0041] The above description points out and describes several preferred embodiments of the present invention, but it should be understood that the present invention is not limited to the form disclosed herein and should not be regarded as excluding other embodiments. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A nanocellulose / aramid fiber lithium battery separator material using a heterogeneous process, characterized in that: Nanocellulose with good lyophilicity and aramid fiber with excellent high temperature resistance are used to modify and prepare nanocellulose and aramid fiber suspensions respectively. After the two suspensions are completely mixed, a polyimide solution is added to blend them. The blended membrane is obtained by sheeting and filtration, and then the surface of the blended membrane is further sprayed with a polyimide solution. After solvent replacement, drying, spraying and drying, a nanocellulose / aramid fiber lithium battery separator material with excellent performance is obtained.

2. The nanocellulose / aramid fiber lithium battery separator material of the heterogeneous process according to claim 1, characterized in that: The lithium battery separator has a thickness of 100 to 350 μm, a mechanical strength of 5 to 55 MPa, an electrolyte absorption rate of 100 to 400%, a liquid retention rate of 50 to 250%, a porosity of 20 to 80%, a separator heat shrinkage rate of 0.2 to 2% at 200° C., a heat shrinkage force of 0.01 to 0.6 N, an ion conductivity of 0.5 to 1.5 mS / cm, and a discharge capacity of 150 to 170 mAh.g at 0.2C. -1 .

3. The nanocellulose / aramid fiber lithium battery separator material of the heterogeneous process according to claim 1, characterized in that: The nanocellulose is nanocellulose extracted from one or more mixed pulps of cotton pulp, wood pulp, bamboo pulp or grass pulp.

4. The nanocellulose / aramid fiber lithium battery separator material of the heterogeneous process according to claim 1, characterized in that: The aramid fiber is one or more mixed fibers selected from pulp, short cuts, staple fibers and dry powder of para- or meta-aromatic aramid fibers.

5. The nanocellulose / aramid fiber lithium battery separator material of the heterogeneous process according to claim 1, characterized in that: The polyimide is one of water-soluble polyimide, homophenyl polyimide, polyamide-imide or polyetherimide.

6. A method for preparing a nanocellulose / aramid fiber lithium battery separator material by a heterogeneous process as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of nanocellulose suspension: first prepare a nanocellulose / cationic polyacrylamide / diatomaceous earth mixed solution, then add solid acid and stir evenly to obtain a suspension; the mass percentage of each component of the suspension is 0.1-0.9% nanocellulose, 0.001%-0.009% cationic polyacrylamide, 0-0.1% diatomaceous earth, 0-10% solid acid, and water is added; the stirring time is 0.5-2h, the stirring temperature is 80-115°C, and the rotation speed is 700-1200rpm; the content of diatomaceous earth and solid acid in the suspension is not 0; (2) Preparation of aramid fiber suspension: prepare an alkaline suspension solution of aramid fiber / polyethylene oxide, wherein the mass percentages of the components of the suspension are aramid fiber 0.3-0.7%, polyethylene oxide 0-0.02%, strong alkali 0.4%-0.6%, and water for the balance; the stirring time is 0.5-2h, the stirring temperature is 20-40°C, and the rotation speed is 200-300rpm; the content of polyethylene oxide in the suspension is not zero; (3) Preparation of blended membrane: after mixing all the suspensions obtained in steps (1) and (2), adding polyimide solution for blending, the concentration of polyimide solution is 0-20%, the mass ratio of polyimide to nanocellulose / aramid fiber is 0-5.5:1, and the blending time is 30-60 min; then the blended solution is sheeted and filtered to form a membrane, and the nanocellulose / aramid fiber blended membrane is obtained through solvent replacement and drying process, the solvent replacement time is 0.25-4 h, the drying time is 0.75-1.5 h, and the drying temperature is 60-90° C.; the concentration of polyimide solution is not 0; (4) Surface spraying treatment of the blended membrane: spray the polyimide solution in step (3) on the surface of the blended membrane obtained in step (3), and then spray it several times after drying to finally obtain a nanocellulose / aramid fiber lithium battery separator. The number of spraying times is 1 to 4 times, the drying time is 20 to 60 minutes, and the drying temperature is 80 to 110°C.

7. The method for preparing a nanocellulose / aramid fiber lithium battery separator material by a heterogeneous process according to claim 6, characterized in that: The solid acid in step (1) is one of glutaric acid, adipic acid or azelaic acid.

8. The method for preparing a nanocellulose / aramid fiber lithium battery separator material by a heterogeneous process according to claim 6, characterized in that: In the step (1), the cationic polyacrylamide is a dry powder having an ionicity between 40 and 60.

9. The method for preparing a nanocellulose / aramid fiber lithium battery separator material by a heterogeneous process according to claim 6, characterized in that: The diatomaceous earth in step (1) is a kind of siliceous rock formed by the sedimentation of diatom remains, and has a particle size of 5 to 20 microns.

10. The method for preparing a nanocellulose / aramid fiber lithium battery separator material by a heterogeneous process according to claim 6, characterized in that: The strong base in step (2) is one of sodium hydroxide, potassium hydroxide or potassium tert-butoxide.

11. The method for preparing a nanocellulose / aramid fiber lithium battery separator material by a heterogeneous process according to claim 6, characterized in that: The polyethylene oxide in step (2) is a water-soluble polymer with a relative molecular weight of 1 to 4 million.

12. The method for preparing a nanocellulose / aramid fiber lithium battery separator material by a heterogeneous process according to claim 6, characterized in that: The solvent in step (3) is one of methanol, ethanol or isopropanol.

Citation Information

Patent Citations

  • Flame-retardant cellulose membrane for lithium battery and preparation method of membrane

    CN103579562A

  • Versatile single-layer lithium ion battery separators having nanofiber and microfiber components

    CN104871341A

  • Lithium battery separator and preparation method and application thereof

    CN107452922A